The Impact of Social Distancing and Physical Distancing Policies in the Management of Artificial Tourism Objects - Novva N. Plangiten; Arie J. Rorong; Shirley Y. V. I. Goni; Salmin Dengo (Borong Newinera Publisher, 2022)
Social distancing and physical distancing policies are actions taken by the government to stop the spread of Covid 19. In its implementation, it has had an impact on the management of artificial tourism objects. The research data was collected directly through the interview process to the managers of artificial tourism objects and tourists directly at the research site. Data collection was also carried out for the government and the Covid 19 task force using the google form. Data was also collected secondaryly by accessing Google Scholar. The presentation of the data in this study was carried out in a descriptive-analytic manner and deductively drawing conclusions. Research findings that the application of social distancing and physical distancing on artificial tourism objects have had a direct or indirect impact on the economic and social aspects.